Modelos de internacionalismo y modernidad. Las artes plásticas paraguayas en la encrucijada brasileña - María Amalia García (Nuevo mundo - Mundos Nuevos, 2014)
This paper studies the artistic promotion of the Paraguayan field through the management of the Brazilian Cultural Mission during the 50s. This research concerns on three main aspects : the exhibitions of Brazilian art shown in Asunción ; the Paraguayan representations at the São Paulo´s Biennials and Lívio Abramo´s activity as a key figure to the Brazilian cultural promotion in Paraguay.